온대자포니카 벼 품종의 등숙기 종자 내 카드뮴 함량에 관한 전장유전체연관분석 - 이상범(Sang-Beom Lee); 김규원(Kyu-Won Kim); 윤민영(Min-Young Yoon); 김경진(Gyeong-Jin Kim); 류지혁(Ji-Hyock Yoo); 김원일(Won-Il Kim); 문병철(Byeong-Churl Moon); 박상원(Sang-Won Park); 박용진(Yong-Jin Park) (Korean journal of breeding, 2016)
Objective of this study was to investigate the difference of cadmium (Cd) levels in rice grains from non-polluted fields and to define the gene associated with Cd uptake for producing safety food. Cd was analyzed by Inductively Coupled Plasma Mass Spectrometer (ICP-MS). The average concentration of Cd in rice grains was 0.943 μg/kg and Cd levels ranged from 0.050 to 5.699 μg/kg. Genome-Wide Association study (GWAS) based on phenotype data for Cd levels was performed. However, results of GWAS were affected by subpopulation structure and caused false positive. Therefore, GWAS for rice ecotypes (temperate Japonica, tropical Japonica, Indica, Aus, Aromatic, and Admixture) was performed to minimize false positive. GWAS results showed that Os01g0611300, Os01g0611900, Os01g0611950, Os01g0612000, Os01g0612200, Os11g0444400, Os11g0444700, Os11g0444800, and Os11g0444900 genes have significant correlation with Cd levels in rice grains. The sequences of these genes were compared to sequence positions of each other gene (haplotype analysis). According to the results of haplotype analysis, Cd levels of non-synonymous group were higher than other groups and sequence of non-synonymous group was similar to that of Indica. These results were corresponding to the previous research result that Cd levels of Indica were higher than Japonica. Therefore, candidate genes detected through GWAS need to be examined by knock-out or cross breeding.